Character, Attitude and Disposition. (20th May 2013) - Webber, Jonathan
Abstract: Recent debate over the empirical psychological presuppositions of virtue ethics has focused on reactive behavioural dispositions. But there are many character traits that cannot be understood properly in this way. Such traits are well described by attitude psychology. Moreover, the findings of attitude psychology support virtue ethics in three ways. First, they confirm the role of habituation in the development of character. Further, they show virtue ethics to be compatible with the situation manipulation experiments at the heart of the recent debate. Finally, they show how the cognitive‐affective theory of personality and the two‐system theory of behavioural cognition are compatible, thereby undermining the current empirical challenge to virtue ethics. Empirical research into the nature and development of attitudes should therefore be central to philosophical discussions of virtue and character.